PERSIAPAN WARGA PANTI DARUSSHOLIHIN MEMASUKI DUNIA KERJA DI ERA DIGITAL - Sih Darmi Astuti; Ana Kadarningsih; Dian Prawitasari (Jurnal Padamu Negeri, 2024)
In the current digital era, there is an imbalance between the number of job seekers and job vacancies in both state and private companies. Tight competition between job seekers demands more skills and expertise as a competitive advantage for job seekers. One thing that job seekers must have is personal branding that highlights the positive qualities of job seekers. Personal branding is an added value or skill to win the job search competition. In this community service activity (PKM), the expected output is that training participants can optimize their abilities, skills and positive values ​​so as to increase personal branding. This community service activity was carried out at the Darussholihin Orphanage, Mranggen, Demak with a total of 65 training participants. The training provided includes public speaking and team building training. This training was provided by the community service team of the Faculty of Economics and Business program, management studies, Dian Nuswantoro University. The aim of the public speaking and team building training is to prepare residents of the Darussholihin Orphanage, Mranggen, Demak to enter the world of work in the digital era. Apart from that, the aim of training and community service activities is to create personal branding for the residents of the Darussholihin Orphanage, Mranggen, Demak so that they have competitiveness in the world of work.